Thou shalt not pass - arachnid venom peptides interacting with biological membranes - Wang, Yachen; Guo, Shaodong; Jee, Katie F.; Herzig, Volker (Frontiers in Arachnid Science, 2024)
Arachnid venom peptides receive increasing attention from researchers for possible applications as human therapeutics, as bioinsecticides in agriculture or for targeting vectors of human disease. One commonly perceived disadvantage of peptides in contrast to small molecule drugs is their inability of crossing biological membranes comprised of lipid bilayers, providing a major obstacle for the delivery of peptide-based drugs and bioinsecticides. However, some arachnid venom peptides were reported to cross biological membranes, including cellular membranes, the vertebrate and insect blood brain barrier (BBB) and the insect midgut epithelium. This review will focus on these membrane-permeating arachnid peptides and discuss the underlying mechanisms. Different physico-chemical properties of membrane-permeating arachnid peptides and their contribution to the ability of crossing biological membranes will also be examined. In addition, several methods that facilitate or enable peptides to cross biological membranes will be discussed, which can be employed on peptides with no inherent membrane-permeating capabilities.